INCIDENCE OF POWDERY MILDEW ON CUCURBIT PLANTS IN KATSINA, NIGERIA - Labo, Abubakar Umar; Gufran Ahmad, Abrar Ahmad Khan (Journal of Phytology, 2019)
Present paper deals with the study of powdery mildew incidence on different cucurbits in Katsina city (Barhim Estate, Kofar Durbi, Kofar Sauri, Kofar Marusa and Low Cost), Nigeria. The finding shows that the areas infested with powdery mildew is one of the important disease of cucurbits. The Sphaerotheca fuliginea was identified to be the causal organism present on all observed cucurbits in the study. Highest frequency of disease was found in Kofar Sauri(79%) fallowed by Kofar Marusa (68%), Kofar Durbi (66%), Barhim Estate (65%) and the lowest frequency of occurrence of disease was found in Low Cost (55%).The intensity of the disease was moderate to severe in general but it was high in many fields, the area-wise variation was also noticed. On vegetables, the highest frequency of occurrence of powdery mildew disease was observed on L. cylindrica (76.4%) followed by C. moschata (60%), C. sativus (59.3%), C. vulgaris (53.9%) and lowest was found on C. melo (44.4%). The highest intensity of disease was found on C. moschata, followed by L. cylindrica, C. sativus, C. vulgaris and C. melo.